2019
DOI: 10.1021/acssuschemeng.8b04688
|View full text |Cite
|
Sign up to set email alerts
|

Water Electrolysis using Flame-Annealed Pencil-Graphite Rods

Abstract: Inexpensive and sensitive graphite electrodes were fabricated by applying flame annealing to pencil-graphite rods (PGRs) as electrodes for water electrolysis cells. The resin (polymer, binder) on the surface of PGR was removed by flame annealing to make it porous, and the graphite electrodes with high activity and low cost were obtained. By flame annealing the PGR, although the PGR electrode became active upon water electrolysis, the PGR electrode became instable for long-time operation. The effects of flame a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
(35 reference statements)
1
17
0
1
Order By: Relevance
“…Hysteresis was observed between forward and reverse potential sweeping directions, which was considered to be the effect of the capacitance of the electrocatalyst on the PGR with a large specific surface area. 10 In addition, this capacitance effect did not change significantly before and after catalyst deposition. This suggested that the catalyst on the PGR surface did not have a porous structure, as observed by SEM (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Hysteresis was observed between forward and reverse potential sweeping directions, which was considered to be the effect of the capacitance of the electrocatalyst on the PGR with a large specific surface area. 10 In addition, this capacitance effect did not change significantly before and after catalyst deposition. This suggested that the catalyst on the PGR surface did not have a porous structure, as observed by SEM (Figure 2).…”
Section: Resultsmentioning
confidence: 91%
“…In this study, a PGR (the hardness: 4B, uni exchangeable pencil graphite rod, φ2.0 mm × 130 mm, Mitsubishi Pencil Co., Ltd., Japan), which is low cost and useful as a base material for the catalyst-deposited electrode, was used as a base material for the catalyst-deposited electrode in water electrolysis. 10 Figure 1a shows the schematic illustration of the fabrication procedure of Pt and RuO x catalysts deposited on a PGR by flame-annealing. The PGR electrodes with Pt and RuO x catalysts were named Pt/PGR and RuO x /PGR, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…'Previous data by SEM and BET showed that ame annealing treatment improves the porosity of PGRs'. 25 We tested FA@PGRs for the OER; however, they were not good catalysts for this reaction. For this reason, in order to improve the performance of PGRs, we developed new electrodes by the deposition of Ni and NiFe on the PGR (Fig.…”
Section: Resultsmentioning
confidence: 99%